Facile oxidation of flavanones to flavones using [hydroxy(tosyloxy)iodo]benzene in an ionic liquid - Muthukrishnan, Murugan; Patil, P. S.; More, Shivaji V.; Joshi, Ramesh A. (Mendeleev Communications, 2005)
A method for the oxidation of flavationes to flavones has been developed using [hydroxy(tosyloxy)iodo] benzene (HTIB) in the room-temperature ionic liquid 1,3-di-n-butylimidazolium bromide ([bbim]Br-+(-)).

First iodocyclization reaction of allene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Jadhav, Amol R.; Lahore, Santosh V.; Kahar, Nilesh M.; Joshi, Rohini R.; Joshi, Ramesh A.; Koketsu, Mamoru (Tetrahedron Letters, 2014)
The regioselective iodocyclization reaction of allene-thioureas is described, for the first time, for the synthesis of bicyclic beta-lactams. The substitution at the allenyl part heavily influenced the iodocyclization reaction. The iodocyclization reaction of the unsubstituted allene-thioureas afforded six-membered 3-thia-1-dethiacephems whereas, the substituted allene-thiourea afforded seven-membered thiazepines along with five-membered isopenams. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Allene; beta-Lactams; Iodocyclization; Regioselective; thiourea

First regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles - Rode, Navnath D.; Sonawane, Amol D.; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P. (Tetrahedron Letters, 2015)
The regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles is described for the first time. The iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles using molecular iodine afforded diiodo-compound which on Cul-catalyzed intramolecular C-N coupling reaction gave six-membered 2-aryl-51141,2,4]triazolo[5,1-b][1,3]thiazines, whereas, the five membered 3-aryl-5,6-dihydrothiazolo[2,3-c][1,2,4]triazoles were obtained exclusively when the iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles was carried out using NIS. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Iodocyclization; Regloselective; Thiazine; Triazole